(untitled) (Journal of Economic Research & Business Administration, 2015)
The share markets are rather sensitive to any political and economic fluctuations in the world. According to existing global tendencies: cyclic deterioration of a conjuncture of the global financial market; crisis processes in peace development of some countries; actualizations of strategic development of the global financial markets, and their expansion to the countries with developing economy causes a basis of the assumption, that the aspiration of the countries to keep the not numerous national financial markets means aspiration to keep a symbol of competitiveness of economy and political stability. In the modern world everyone is maximum to aspire to increase the own capital, both at a micro level, and on international scene. If the capital is stable and has potential to augmentation its owner is stable and significant. The law of evolution of participants of a history of XXI century is those. Realities of our time dictate banks is systematized to organize and effectively to operate an investment portfolio. In article attempt of formation of recommendations for commercial banks concerning to their efficient control an investment portfolio is undertaken.